Resistivity Study of Shallow Aquifers in theParts of Southern Ukanafun Local Government Area, Akwa Ibom State, Nigeria - N. J. George; A. E. Akpan; I. B. Obot (E-Journal of Chemistry)
A resistivity study by vertical electrical sounding (VES) employing the Schlumberger electrode configuration has been used to delineate shallow aquifers in some villages in Southern Ukanafun Local Government Area of Akwa Ibom State, Southern Nigeria. The information realized from the resistivity data and nearby logged boreholes show that the depths penetrated by currents were all sandy formations with various thicknesses. However, the main aquifers comprise within the maximum current penetration, very coarse – grained (gravelly) sand and fine sand with resistivity in the ranges of 4680-30700 Ωm and 207-2530 Ωm and thickness in the ranges of 43-63 m and 18-40 m respectively. The aquifers with minor hydraulic gradient are separated by thin beds of clay according to lithology logs and these beds were masked in the sounding data due to the principle of suppression.